The Five Levels of Leadership - Maxwell, John C. (GHQ, Rawalpindi Services Book Club, 2013)
True leadership isn't a matter of having a certain job or title. In fact, being chosen for a position is only the first of the five levels every effective leader achieves. To become more than "the boss" people follow only because they are required to, you have to master the ability to invest in people and inspire them. To grow further in your role, you must achieve results and build a team that produces. You need to help people to develop their skills to become leaders in their own right. And if you have the skill and dedication, you can reach the pinnacle of leadership-where experience will allow you to extend your influence beyond your immediate reach and time for the benefit of others. The 5 Levels of Leadership are: 1. Position - People follow because they have to. 2. Permission - People follow because they want to. 3. Production - People follow because of what you have done for the organization. 4. People Development - People follow because of what you have done for them personally. 5. Pinnacle - People follow because of who you are and what you represent. Through humor, in-depth insight, and examples, internationally recognized leadership expert John C. Maxwell describes each of these stages of leadership. He shows you how to master each level and rise up to the next to become a more influential, respected, and successful leader. - Publisher.
Include Notes.
John C. Maxwell is the New York Times Bestselling Author.
Keywords: Leadership -- Business -- Management -- Success in Business -- Time Management -- Leadership--Psychological Aspects